The Effect of Profitability, Leverage, and Liquidity on Company Value - Rafli Irham Al-fafa Suharto; Imron Rosyadi (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2023)
The study aims to analyze the effect of profitability, leverage, and liquidity on firm value, a case study of manufacturing companies listed on the Indonesia Stock Exchange. This research method is quantitative. This research approach is quantitative because the data used comes from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021 whose data contains a number of numbers or numbers. Purposive sampling was used in the sampling technique. The data analysis used is the classical assumption test, multiple linear regression analysis, determination test, and partial hypothesis testing with the T-test and simultaneously with the test. The results and discussion of the research are profitability ratios, liquidity has a negative and insignificant effect on firm value. The leverage ratio has a positive and significant effect on firm value. Profitability, leverage, and liquidity ratios together have a positive and significant effect on firm value. The conclusion of this study is that there is a significant effect of profitability, leverage, and liquidity ratios on the value of manufacturing companies listed on the IDX.